Solid oxide fuel cell anode surface modification by magnetron sputtering of NiO/YSZ thin film; Energy Fluxes and Radiation Effects (EFRE-2016) - Ionov I. V. Igor Vyacheslavovich; Soloviev A. A. Andrey Aleksandrovich; Lebedinsky A. M. Aleksey Mikhaylovich; Shipilova A. V. Anna Viktorovna; Smolyanskiy (Smolyansky, Smolyanskii) E. A. Egor Aleksandrovich; Lauk A. L. Aleksandr Lukyanovich; Remnev G. E. Gennady Efimovich (2016, 2016)
Title screen